Giant paratubal cyst presenting as adnexal torsion: A case report - Filipa Alpendre; Isabel Pedrosa; Rita Silva; Serafim Batista; Paula Tapadinhas (Case Reports in Women's Health, 2020)
Background: Paraovarian/paratubal cysts constitute about 10% of adnexal masses and are usually small and asymptomatic. A huge paratubal cyst complicated by adnexal torsion is a rare cause of acute low abdominal pain. Case Report: We report the case of an obese 31-year-old nulliparous woman who presented with a large pelvic cyst causing ovarian torsion. The size of the mass (~25 cm) caused pain, and obesity led to explorative laparotomy, which showed a huge central abdominal-pelvic cyst arising from the right adnexa. Cystectomy was technically impossible, so all the adnexa was removed. Pathologic diagnosis revealed a papillary serous cystadenoma with torsion of all structures. Conclusion: A giant paratubal cystadenoma is a rare condition and management is challenging. If there are clinical and imaging signs of torsion, it should be approached like any other adnexal mass and surgery should be urgent in order to avoid irremediable compromise of ovarian function.